THE SANGHYANG JARAN DANCE IN NYALIAN VILLAGE, KLUNGKUNG, AS A SOURCE OF INSPIRATION FOR THE CREATION OF VISUAL ART WORKS - Darmasuta, I Putu Eka; Setem, I Wayan; Adi Sucipta, I Wayan (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2026)
The report on the creation of this work of pure art was inspired by the Sanghyang Jaran dance in Nyalian Village, Banjarangkan District, Klungkung Regency. As a source of inspiration for creative ideas, the author has lived side by side with the Balinese customs and traditions around him since childhood, and one of them is the Sanghyang Jaran dance. The Sanghyang Jaran dance is also a religious art because it involves the spirit of Sanghyang Jaran, which will possess the selected dancer and will experience a trance, and Sanghyang Jaran dance performances are held at several temples. is in Nyalian Village. The creation process used stages: basic research, exploration, canvas experiments with acrylic paint totaling 4 (four) works, and 2 (two) works of wood-based sculpture. In the process of creating the work, the author took references from the Wasundari Kamasan studio as a source for creating the work. The author combines the ornaments given. In the creation process, the author took the form of patterns, proportions of rock shapes, standards, and several other techniques.